Ayurvedic Treatment Regime of Ovarian Hemorrhagic Cyst: A Case Report. - Deepika; Kumar, Arun; Tanwar, Suniti (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Women’s life hormones play an important role from menarche to menopause. Abnormality in the ovarian hormones in co-ordination with HPO axis influences her physical, psychological and reproductive health. Abnormal food habits and altered life have influence on secretion of female hormones and there by lead to manifestation of ovarian cyst. Hemorrhagic ovarian cyst is commonly encountered in day-to-day gynaecological practice. Methodology: In this present case study, a 36 years old woman patient consulted to the OPD with the complaint of pain in lower abdomen, Irregular menses and generalized weakness. She had also brought her ultrasonography (USG) and finding suggested a left ovarian haemorrhagic cyst measuring 44mm × 36 mm. She was supposed to be treated with traditional ayurvedic formulations; the case was treated for three months with a combination of different traditional Ayurvedic drugs, with the goal of relieving symptoms and dissolving the ovarian cyst. This patient was treatedwith traditional Ayurvedic formulations like Sukumar Kashyam, Kanchnar guggulu, Dashmoola kwatha, Yavkshara, Ajmoodadi choorna. Result: Only traditional Ayurvedic medicines were used during the course of the treatment. Follow-up USG showed complete disappearance of cyst and symptoms also subsided to a great extent. Discussion: The present study emphasizes the role of Ayurveda in bringing a positive result in the management of ovarian cyst.